Measurements on the external load acting on aquatic resistance fins during flexion/extension movements using a robotic joint - Gislason, M. K.; Einarsson, I. T.; Ingvason, S. S.; Saavedra, J. M; Waller, B. (Frontiers in Physiology, 2022)
Aquatic resistance training has been proven to be beneficial to many people, in particular, those struggling with degenerative joint diseases or recovering from other musculoskeletal issues as the reaction forces acting on the joints become lower, but without compromising the cardiovascular and neuromuscular benefit of the movement. Little has been written on the load produced by or measurements on devices used in aquatic resistance training. Therefore, uncertainties exist regarding terms of how much load is applied onto the foot when performing the movements and how to quantify progression. In the presented study, an instrumented robotic arm was designed, built, and used to measure the load acting on the three different types of fins during a simulated flexion/extension movement of a knee. The angular velocities of the knee ranged from 25°/s to 150°/s which represent the physiological range of in vivo movements. The results demonstrated that the load followed a second-order polynomial with the angular velocities. The load is therefore a function of the angular velocity, the surface area of the fins, and the location of the fins away from the joint center rotation. We modeled the progression of speeds at maximal voluntary movements based on previous studies. The maximum loads measured between 11kg and 13kg in extension and 6kg and 9kg in flexion at 150°/s rotational velocity.